Ādhunika Hindī mahākāvyoṃ meṃ pāścātya cintana - Sainī, Rāmakiśana, 1944- (Pañcaśīla Prakāśana, 1980)
On the influence of western poetical and socio-political thoughts on modern Hindi literature in general and epic poetry in particular.